Elucidation of stereochemistry by N.M.R. spectroscopy. - Zamora, Cesar Reyes. (University of Ottawa (Canada), 1968)
The analysis of the N.M.R. spectra of a series of substituted 1,4-dioxanes showed the following configurations and conformations for the compounds: 2,3-dichloro-1,4-dioxane m.p. 52°, 2,3-diphenyl-1,4-dioxane m.p. 132° and naphtodioxane have the cis configuration and at room temperature are rapidly interconverting between chair conformations; 4a,8a-dimethoxy-4a,8a-dihydro-1,4-benzodioxan and 4a,8a-dimethoxy-4a,5,6,7,8,8a-hexahydro-1,4-benzodioxan have the trans configuration with a rigid chair conformation. Non-equivalence in the vicinal coupling constants JAX and JBX were found for 2,2,2-trifluoroethyl-2-tetrahydrofuranyl ether and 2,2,2-trifluoroethyl-2-tetrahydrofuranyl ether and 2,2,2-trifluoroethyl-2-tetrahydrothiapyranyl ether as found previously for 2,2,2-trifluoroethyl-2-tetrahydrofuranyl ether by Dr. R.R. Fraser and P. Hanbury. No definite conclusion regarding the origin of this non-equivalence could be drawn from the results. Linear Hammett plots were obtained in a study of the effect of substituents on the chemical shift of the methylene protons in para-substituted benzyl phenyl sulfides, sulfoxides and sulfones. It has been found that the protons in the methylene group are affected very differently by the substituent in each series. The causes for this variation have been examined and it is proposed that the effect is conformational. In the conformation in which a C-H bond is paralled to the adjacent p-orbital of the benzene ring, that C-H proton will experience the maximum substituent effect.
Keywords: Chemistry, Analytical.